2014
DOI: 10.3103/s0967091214060151
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of low-alloy Cr-Mo-V steel after austenitization in the intercritical temperature range

Abstract: The structure formation in steel as a result of double quenching (the second time from the intercritical temperature range A c1 -A c2 ) and high tempering is established. By EBSD, the crystallo graphic features of the ferritic-martensitic structure formed in single and double quenching and stabilized on tempering are studied. The prospects for improving the mechanical properties of low alloy, low carbon Cr⎯Mo-V steel by quenching from the intercritical temperature range are considered Keywords: low alloy low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…This spectrum resulted from austenite transformation by shear mechanism according to orientation relationships, intermediate between K-S OR and N-W OR, in accordance with [15]. Such special boundary spectra were also detected in martensite of low-carbon tube steel [16]. Detailed examination of CSL boundary areas showed that Σ3 boundary is mainly fixed between parallel laths of one package (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…This spectrum resulted from austenite transformation by shear mechanism according to orientation relationships, intermediate between K-S OR and N-W OR, in accordance with [15]. Such special boundary spectra were also detected in martensite of low-carbon tube steel [16]. Detailed examination of CSL boundary areas showed that Σ3 boundary is mainly fixed between parallel laths of one package (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…1, e, Nishiyama-Wasserman types, as shown in [11]. Such spectra of special boundaries are also seen in the martensite of low-carbon pipe steel [12,13].…”
Section: Resultsmentioning
confidence: 78%
“…In paper [21] it was shown that this spectrum results from martensite phase transformation according to orientation relationships intermediate between K-S and N-W. Such CSL boundary spectra were also registered in both martensite and bainite of low-carbon tube steels [19,22]. Analysis of crystallographic interaction between α-phase crystallites and neighbouring austenite grains (Fig.…”
Section: Resultsmentioning
confidence: 88%